Combined toxicity of multiwall carbon nanotubes and cadmium on rice (Oryza sativa L.) growth in soil - Long, Jinghua; Wang, Xuanxuan; Zhang, Wei (Frontiers in Environmental Science, 2024)
The comprehensive effects of nanoparticles and coexisting heavy metals on plant growth are still unclear, especially in soil medium. The single and combined effects of multiwall carbon nanotubes (MWCNTs) and cadmium (Cd) on rice (Oryza sativa L.) growth were examined in this study through a four months pot experiment in 2022. Rice plants were exposed to different concentrations of MWCNTs (100 and 500 mg kg -1 ) in the presence of 5.0 mg kg -1 Cd stress. At the tillering stage, the 500 mg kg -1 MWCNTs addition reduced plant height by 8.0% and increased soluble protein content in the leaves by 13.7%, demonstrating that a single MWCNTs had a slight negative impact on rice growth. When exposed to Cd stress, the inclusion of 500 mg kg -1 MWCNTs led to a 6.7-9.0% decrease in bioavailable Cd level in soil, resulting in considerable reductions in Cd content in roots (23.4-29.9%), shoots (24.5-28.3%) and grains (28.3-66.2%). Compared to the single Cd treatment, the Oryza sativa L. leaves treated with Cd and MWCNTs (500 mg kg -1 ) had considerably reduced levels of malondialdehyde (MDA), soluble protein, and activities of antioxidant enzymes (POD, CAT, and SOD). The findings of this study indicated that appropriate concentrations of MWCNTs application in soil could alleviate Cd-induced toxicity on rice growth.